A GA-based optimization for Fourth-order Sallen-Key low-pass filter - Neoh, Siew Chin, Dr.; Teoh, Yeong Yeap (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org